Special morphological papillary glioneuronal tumor - Ding⁃rong ZHONG; Yu ZHAO; Jie GAO; Xuan ZENG; Wen⁃bin MA (Chinese Journal of Contemporary Neurology and Neurosurgery, 2010)
Objective To report a case of special morphological papillary glioneuronal tumor of central nervous system with its cytology, histopathology, ultrastructure and molecular genetics changes. Methods Retrospective study was performed to analyse the clinical manifestations, imaging characteristics, cytologic and histopathologic and ultrastructure findings. Immunohistochemical staining and fluorescence in situ hybridzation (FISH) detecting were done to the tumor tissue. Results The main clinical manifestations were headache, dizziness accompanied by nausea, vomiting in short course. MRI revealed a huge cystic and solid space⁃occupying with enhanced solid part in brain parenchyma of right frontotemporal lobe. The fresh tumor tissue imprint showed papillary structure with blood vessel core and ganglion⁃like tumor cells. Histopathologic examination revealed clear boundary between tumor tissue and the normal white matter. The local ganglion⁃like tumor cells were arranged in sheet with scattered ganglion cells and eosinophilic granular bodies, and some pseudopapillary tumor cells were arranged around the vessel wall thickened with hyalinization. Ultrastructure showed that the tumor cells with cytoplasm⁃rich and prominent nucleoli contained many rough endoplasmic reticulums and ribosomes. Tumor cells showed diffuse strong positive expression of vimentin (Vim), CD34 and nestin (Nes). Papillary tumor cells were positive for AE1/AE3 and epithelial membrance antigen (EMA), focal sheet cells expressed neurofilament (NF), CD56, synaptophysin (Syn) and glial fibrillary acidic protein (GFAP). Only few cells were P53 ⁃ positive and mean Ki ⁃ 67 index of tumor cells was about 3% . FISH test showed that there were some polyploid tumor cells, but without amplification of epidermal growth factor receptor (EGFR), EGFR⁃1 and human epidermal growth factor receptor ⁃ 2/topoisomerase Ⅱ (HER ⁃ 2/Topo Ⅱ). Due to a small amount of residual tumor, the patient received radiotherapy and no recurrence signs were detected after follow ⁃ up of 20 months. Conclusion This tumor shows features of papillary glioneuronal tumor, but with some solid sheet area and special immunohistochemical expression, so we recommend that using a new subtype of papillary glioneuronal tumor—solid⁃pseudopapillary subtype names this tumor. This kind of tumor should be further followed up.